Polarization converter for higher-order laser beams based on the use of forming binary diffractive optical elements as beam splitter - Sergey V Karpeev; Svetlana N Khonina; Oleg Yu Moiseev; Sergey V Alferov; Aleksey V Volkov (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2012)
We propose a new approach to generating a pair of initial beams for a polarization converter that operates by summing up two opposite-sign circularly polarized beams. The conjugated pairs of vortex beams matched with laser modes are generated using binary diﬀractive optical elements. The same binary element simultaneously serves two functions: a beam shaper and a beam splitter. Two proposed optical arrangements are compared in terms of alignment complexity and energy eﬃciency. The diffractive optical elements in question have been designed and fabricated. Natural experiments that demonstrate the generation of vector higher-order cylindrical beams have been conducted.